Model Asesmen Diagnostik Pembelajaran: Upaya Meningkatkan Pembelajaran Bermutu dan Berpusat pada Siswa - Rida Rimadani; Sumiatun Sumiatun (MASALIQ, 2025)
Students’ interest and readiness to learn have declined in the post-pandemic period, while the implementation of the Kurikulum Merdeka requires a differentiated, student-centered learning approach. In this context, the practice of diagnostic assessment as a foundation for mapping learning needs has yet to be optimally implemented in many schools. This study aims to describe the implementation of cognitive and non-cognitive diagnostic assessments and their utilization in designing meaningful learning. A qualitative approach with a case study design was conducted at SMPS Islam Terpadu Al Bashiroh, Malang. Data were collected through in-depth interviews with the Vice Principal for Curriculum and the Guidance and Counseling teacher, along with document analysis of assessment results. Descriptive analysis was used to map out the implementation procedures, key findings, and instructional follow-up. The findings reveal that (1) cognitive diagnostic assessments are conducted at the beginning of new topics and at the end of instruction through written tests and observation, aimed at identifying prerequisite knowledge, misconceptions, and students' learning readiness; (2) non-cognitive assessments are carried out through learning style inventories (visual, auditory, kinesthetic) and structured interviews to explore students’ preferences, emotions, and learning contexts; (3) assessment results are used by teachers to design differentiation strategies in content, process, and learning products. The study concludes that diagnostic assessments play an effective role in guiding lesson planning tailored to individual student needs and enhancing the quality of the learning process. Practical implications include the need for structured diagnostic assessment policies, teacher capacity-building in instrument development and data analysis, integration of assessment results into lesson planning, and the use of data for remediation, enrichment, and parent communication.